Detección de coproantígenos de fasciola hepatica en ovinos del Cocuy, Boyacá - Flechas Bernal, Juan Diego (Universidad Pedagógica y Tecnológica de Colombia, 2024)
Eng: Fasciola hepatica, a trematode that parasitizes the bile ducts of ruminants and humans, is considered one of the most important endoparasites within animal production systems for causing productive losses, since being hematophagous, the parasite produces states of anemia, emaciation and cachexia in the host; Additionally, infections by this trematode have an economic impact generated by the costs associated with treatment and by the confiscation of organs at slaughter to avoid food transmission. The objective of the present investigation was to identify coproantigens of F. hepatica in sheep from the municipality of Cocuy, Boyacá. A cross-sectional study was carried out, with a sample size of 373 sheep. Approximately 20g of fecal matter was collected from each animal directly from the rectum and refrigerated at 4°C during transport to the laboratory, where they were processed using the commercial kit MONOSCREEN Ag ELISA Fasciola hepatica REF: BIO K201/2 following the instructions of the maker; Subsequently, a statistical analysis was carried out with the EpiInfoTM program. A general prevalence of 12.87% (48/373) was considered, where females (13.31%), sheep between 1-3 years old (16.43%) and Colombian Creole Moorish sheep (15.22%) had a higher prevalence compared to the other groups. The consumption of water from pipes or streams (p= 0.04258132) and the presence of cattle in production (p= 0.02023329) had a significant statistical association with the presentation of F. hepatica. Using logistic regression, it is determined that sheep aged 1–3 years are risk factors for the presentation of F. hepatica in sheep from Cocuy, Boyacá. The existence of an active infection by F. hepatica in a considerable percentage of animals is demonstrated, which indicates a possible endemicity of the parasite in the area and demonstrates the importance of implementing prevention and control strategies to promote the profitability of production, as well as also help protect public health